2012
DOI: 10.1007/s10995-012-1015-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Intimate Partner Violence Among Pregnant Women Attending Kisumu District Hospital, Kenya

Abstract: To determine prevalence and factors associated with intimate partner violence (IPV) among pregnant women seeking antenatal care. This was a cross-sectional study conducted at Kisumu District Hospital, Kenya amongst randomly selected pregnant women. A structured questionnaire was used to collect data. Participants self-reported about their own IPV experience (lifetime, 12 months prior to and during index pregnancy) and associated risk factors. Data were analyzed using Epi-info. The mean age of the 300 participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

67
151
21
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(241 citation statements)
references
References 20 publications
67
151
21
2
Order By: Relevance
“…This is consistent with study done in Kenya and Bangladesh which showed that partner who attends tertiary education is protective against intimate partner violence during pregnancy and husband's education beyond 10th grade was associated in both rural and urban with lower odds of violence during pregnancy [9] [12] [14]. This could be due to when partner education status increase the ability to negotiate may increase and as a result the violence will decrease.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with study done in Kenya and Bangladesh which showed that partner who attends tertiary education is protective against intimate partner violence during pregnancy and husband's education beyond 10th grade was associated in both rural and urban with lower odds of violence during pregnancy [9] [12] [14]. This could be due to when partner education status increase the ability to negotiate may increase and as a result the violence will decrease.…”
Section: Discussionsupporting
confidence: 89%
“…The overall prevalence of intimate violence during pregnancy and prevalence of psychological violence in current study is lower than Kenyan study which showed that the prevalence of intimate partner violence during pregnancy was 37% and the prevalence of psychological violence being 29%. The prevalence of physical violence in current study is higher than the Kenyan study but prevalence of sexual violence is consistent, which showed that sexual 12% and physical 10% [9]. The difference may be due to the difference in culture and norms between the two countries.…”
Section: Discussioncontrasting
confidence: 51%
“…However, other forms of violence (sexual, moral and psychological) were identified. Studies corroborate these results in pointing out that the standard of IPV during pregnancy can be changed in the form, frequency and severity, particularly where violence existed before pregnancy (7,(10)(11)14) .…”
Section: Discussionmentioning
confidence: 55%
“…However, studies confirm that the age group, economic dependence, level of education, use of legal and/or illegal drugs by a woman and her intimate partner are elements that can contribute to the phenomenon (6)(7)21) . It is noteworthy that in this study there was no report of drug use by participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation